Análise da acessibilidade do Parque Natural Municipal Victório Squierolli (Uberlândia/MG) para visitação de pessoas com deficiências física, auditiva e visual - Lima, Ana Beatriz Leça de (2016)
The accessibility for park users with disabilities is rarely addressed. When it is addressed, the types of disabilities are treated individually. However, it is noteworthy that public spaces and services are used by all categories simultaneously. Due to that fact, the main purpose of this work is to analyze the accessibility for three types of disabilities: physical, hearing and visual. This was done in the facilities and activities offered by the Parque Natural Municipal Victório Siquierolli, located in Uberlândia / Minas Gerais. This is a relevant place in non-formal environmental education, offering activities for local schools, researchers and society in general; which also supports the research and extension activities of the Federal University of Uberlândia. Although the location has some access for wheelchair users, there is no specific accessibility project for other disabilities. The research methodology was divided into literature review and documentary research and field research. Field research included direct observation through photographic registration of the park structures using as a gathering instrument, a protocol based on Brazilian Standard NBR 9050/2015, profiling the mediators working in the park and the from the perspective of three associations for each type of disability of this study, through semi-structured interviews. With the results, we can notice that the park does not have all the structures for accessibility that NBR 9050/2015 standard requires, and the present structures, such as ramps, signs, handicap restrooms and free space for movement are not entirely suitable, with a view only to assist people with physical disabilities, more specifically wheelchair users. So necessary adjustments should be done to benefit other disability categories cited in this study, in order to improve the structure of the park and as a consequence increase and diversify the visitors.